Doxorubicin (DOX) modified zinc oxide (ZnO) nanocomposite encapsulated with polymethyl methacrylate (PMMA) biopolymer for effective cancer treatment - Abinash Das; Sampad Ghosh; Pijush Bisal; Nabakumar Pramanik (Results in Surfaces and Interfaces)
Cancer, characterized by uncontrolled cell growth, has conventionally been managed through chemotherapy, radiation, and surgery. However, these approaches often entail systemic toxicity and resistance, necessitating the exploration of alternative strategies like nanotechnology to enhance early detection and targeted drug delivery, thereby reducing side effects. Immunotherapeutic agents utilizing nanomaterials such as zinc oxide nanoparticles, polymeric micelles, and liposomes have emerged as promising tools in cancer treatment by selectively targeting malignant cells while minimizing harm to healthy tissues. Among these, zinc oxide nanoparticles have garnered particular attention for their versatility in biomedical applications, especially in cancer research. In this study, zinc oxide nanoparticles were synthesized using the chemical precipitation method, followed by their encapsulation with the anticancer drug doxorubicin (DOX) and the biopolymer Poly(methyl methacrylate) (PMMA) to create a novel DOX-ZnO-PMMA nanocomposite via a solution-based approach. This innovative strategy holds promise for improving the specificity and efficacy of cancer treatment while minimizing adverse effects on healthy tissues.